2021
DOI: 10.3390/cells10092430
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Assisted Identification of Genetic Factors Predisposing High-Risk Individuals to Asymptomatic Heart Failure

Abstract: Heart failure (HF) is a global pandemic public health burden affecting one in five of the general population in their lifetime. For high-risk individuals, early detection and prediction of HF progression reduces hospitalizations, reduces mortality, improves the individual’s quality of life, and reduces associated medical costs. In using an artificial intelligence (AI)-assisted genome-wide association study of a single nucleotide polymorphism (SNP) database from 117 asymptomatic high-risk individuals, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Due to the multifactorial disease mechanisms also involving genetic factors, exuberant amounts of data accumulate that require machine learning techniques for meaningful conclusions. Here, Yang et al employ a combination of artificial intelligence-assisted identifications of single nucleotide polymorphisms and clinical parameters to identify asymptomatic high-risk subjects that are predisposed to heart failure [35].…”
Section: Computational Simulation Of Electrical Remodellingmentioning
confidence: 99%
“…Due to the multifactorial disease mechanisms also involving genetic factors, exuberant amounts of data accumulate that require machine learning techniques for meaningful conclusions. Here, Yang et al employ a combination of artificial intelligence-assisted identifications of single nucleotide polymorphisms and clinical parameters to identify asymptomatic high-risk subjects that are predisposed to heart failure [35].…”
Section: Computational Simulation Of Electrical Remodellingmentioning
confidence: 99%
“…In addition to involvement in cancer and infectious disease, mutations, or changes in Dock180 activity are likely to be involved in additional developmental defects and pathological processes. Whole genome sequencing and GWAS studies have identified alterations in the Dock180 gene in various pathologies, but the involvement of Dock180 in these processes remains to be confirmed, and mechanisms of action have yet to be investigated [ 74 , 75 , 76 ].…”
Section: Dock180 In Pathological Processesmentioning
confidence: 99%
“…The medical applications of AI are constantly evolving in research clinimetrics while taking over human-based decisions in systems' operations or the diagnosis and treatment of diseases. For example, electronic health record-derived databases processed through machine learning algorithms can facilitate patient care allocation and novel biomarkers research or support genomics to discover disease associations or contain microbial outbreaks (1)(2)(3).…”
mentioning
confidence: 99%